VITAMIN D DEFICIENCY–AN EMERGING PUBLIC HEALTH PROBLEM IN PAKISTAN - Zahid Masood; Qaiser Mahmood et al. (Journal of University Medical & Dental College, 1970)
ABSTRACT Objectives 1. To study the Prevalence of Vitamin D deficiency in the sample population. 2. To study the correlation of Serum Ca, Phosphorus and Alkaline Phosphatase with Vitamin D Deficiency in sample population. Study Design Descriptive Study Setting Local Private Clinic from 1st May to 30th Nov 2009. Material and Methods 600 subjects in the sample included 300 males and 300 females presenting due to any illness or subjects with or without body aches were enrolled. Blood samples were collected in the morning (over night fasting sample) by venepuncture by disposable syringes and 5 ml blood sample was taken and samples were stored at -20 0 C till they were analyzed . Variable of interest were age, gender, serum calcium, phosphate, alkaline phosphatase, serum vitamin D levels and history of bone or body aches. The study was analyzed on SPSS-Version-10 for windows. P – Value < 0.05 was considered statistically significant. Results Results reflected that 77.50% of the sample showed Vitamin D deficiency. Further 18% were in the category of Vitamin D insufficient. Only 4.5% were having values in the normal range. Overall prevalence of Vitamin D deficiency and insufficiency was 95.5%. Among the sample patients only 185 (30.83%) were having bone or body aches as a presenting feature while remaining 415 individuals (69.16%) were having no pains. In our sample all had normal values for serum Ca and Phosphates. However, only 20 patients had modestly elevated level of serum alkaline phosphatase. Conclusion Prevalence of Vitamin D deficiency is of magnitude which poses a public health problem. It is suggested that due to its multi system implications patients presenting with different signs & symptoms and especially when to establish a diagnosis is difficult, serum Vitamin D3 levels may be requested. Health education should be imparted to population and awareness should be created to increase the exposure to sunlight to permissible limits. Screening and vitamin D supplementation should be planned to decrease its varied and multidimensional ill effects on health.